Adsorptive Removal of Dyes: A Comparison of Graphene Oxide to Granular Activated Carbon and Zeolite NaY - Niloufar Nekouei Marnani; F. Handan Tezel; Onita D. Basu (Applied Sciences)
Synthetic carbon-based compounds are a prevalent wastewater contaminant that can adversely impact water resources due to their potential carcinogenic and toxic effects on aquatic biota and human health. This research investigates the versatility of graphene oxide (GO) as an alternative to commonly used adsorbents (zeolite NaY (NaY) and granular activated carbon (GAC)) for removal of synthetic cationic dyes. Rhodamine B (RhB) and methylene blue (MB), were selected as the target contaminants to represent cationic synthetic dyes with differing molecular sizes and structural compositions. Batch experiments using GO, NaY, and GAC as adsorbents were used to assess both physicochemical interactions between adsorbent surfaces and contaminants, and removal efficiency. GO demonstrated the highest removal efficiency for both target contaminants—at 99% and 86%, respectively—while the lowest removal efficiency was observed for NaY. Langmuir, Freundlich, Temkin, and BET isotherm models were used to describe the adsorption isotherms. Overall, GO demonstrated a more robust and higher removal efficiency of cationic dyes compared with GAC and NaY, indicating the potential of graphene oxide for the removal of complex structured organic contaminants in wastewater treatment.